2015
DOI: 10.1016/j.ijgo.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of clinical documentation in India's JSY cash transfer program for facility births in Madhya Pradesh

Abstract: Objective: To gain insight into the quality of care in facilities implementing the Janani Suraksha Yojana (JSY) cash transfer program in Madhya Pradesh, India, by reviewing the level of documentation in the clinical records of women who delivered. Methods: The present retrospective, descriptive study reviewed case records of women who delivered at 73 primary, secondary, and tertiary level facilities in three districts of Madhya Pradesh between 2012 and 2013. Twenty elements of care were assessed encompassing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 17 publications
0
21
1
Order By: Relevance
“… 18 , 23 The uptake of delivery record usage was substantial. Documentation levels were higher than that observed elsewhere in a cross-sectional study in India 6 and in a quality improvement interventional setting in Ecuador. 8…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“… 18 , 23 The uptake of delivery record usage was substantial. Documentation levels were higher than that observed elsewhere in a cross-sectional study in India 6 and in a quality improvement interventional setting in Ecuador. 8…”
Section: Discussioncontrasting
confidence: 80%
“…2 , 3 Suboptimal medical record documentation, however, remains a pervasive problem hampering efforts to improve quality of care offered in resource-limited settings, 4 , 5 with only a minority of parturient women in India having their clinical parameters being documented currently. 6 These are due to several issues: a “culture of nondocumentation,” gaps in knowledge/skills of attending doctors/nurses, inadequacies in the labor room case sheet (open-ended and user nonfriendly), and deficiencies in the health systems (lack of medical records departments, inadequate supply of paper records, etc). 2 , 7 Documentation improvement efforts in other developing countries appear to be promising.…”
Section: Introductionmentioning
confidence: 99%
“…Shortage of dedicated, skilled staff to handle the record, with or without computers, has been documented and it is expected that once they are placed in proper positions; things would improve. 27,33 As reported, information about the scheme was fairly extensive in the districts surveyed. It was communicated where the beneficiaries were possibly contacted, both through inter-personal conversation as well as through various mass approaches.…”
Section: Discussionmentioning
confidence: 93%
“…32 Concern about the deplorable state of record keeping was found in Madhya Pradesh as well. 33 In this study we found an attempt to computerize the various data, like those for identification of beneficiaries; but it was not universal. The condition was somewhat better in terms of regular updating of the dedicated cash registers at different levels of hospitals, where from payment was made.…”
Section: Discussionmentioning
confidence: 99%
“…And, it is associated with increasing institutional delivery among the most deprived groups of people. Further, it has significantly improved institutional delivery in the low performing states (EAGs states) in the last one decade 2005-2015, however, the state and regional level variations still continue to persist [20][21][22][23][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%